Analysis of Menoreh Coffee Sales Strategy in Kulon Progo - Sutoyo; Sutomo; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Study This aim for know strategy And constraint in marketing incised coffee. Type study Which used is qualitative research with descriptive research type. Result of study This show that Menoreh Coffee has implementing a marketing mix strategy that uses the 4P variable that is Products, price, place And Promotions Which capable increase profit And sale product incised coffee. Study This Also there is factor supporters And factor inhibitor application strategy marketing to sale incised coffee products. Which become factor supporters that is support from the community, good service and management the good one. While the factors that hinder the implementation of the strategy marketing on product Menoreh Coffee is Not yet formed structure organization Which Good, power Work or source Power that human still low